Implementation of Educational Media With Role Play Towards Improving Mother Skills As An Effort To Prevent Sexual Violence In Pre-School-Age Children - Laili, Nurul; Handayani, Erna; Ro’isah; Salam, Ainul Yaqin (Chakra Brahmanda Lentera Institute, 2023)
Background: Sexual violence against children is a form of sexual deviation that is very life-threatening, especially because it has a destructive and psychological impact. Meanwhile, in Probolinggo Regency, there are 35 cases of sexual violence against children. The study aims to enhance the effectiveness of educational media in enhancing mothers' abilities to prevent sexual violence in preschool children. The study employs a role-playing game as its educational medium. Methods: The main goal of this study is to evaluate the efficacy of teaching mothers skills in preventing sexual assault with preschoolers through role-playing. This study has a quasi-experimental design. Seventy-six respondents were included in the purposive sampling, of whom 38 were assigned to the intervention group and 38 to the control group. Data were gathered using a questionnaire about the characteristics of the respondents and an observation sheet on